2021
DOI: 10.1097/nmd.0000000000001366
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Burden of HIV Infection and First-Episode Psychosis in Africa

Abstract: A systematic review and meta-analysis was conducted to synthesize data on HIV prevalence in individuals with first-episode psychosis (FEP) and to provide an overview of the association of HIV with clinical variables of FEP. Electronic databases were searched for quantitative studies published from January 1986 to November 2019. Meta-analyses were undertaken to calculate the pooled HIV/FEP proportion based on random effects modeling with inverse variance method. Seven HIV/FEP studies from sub-Sahara Africa (SSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…1 The prevalence in this study is also lower than the estimated 26% rate in the recent systematic review of HIV prevalence in FEP in Africa. 7 Hopefully, the results of this study suggest that HIV prevalence is decreasing in those who are mentally ill and moving towards the general population rates, but this will need to be explored further in larger prospective studies.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…1 The prevalence in this study is also lower than the estimated 26% rate in the recent systematic review of HIV prevalence in FEP in Africa. 7 Hopefully, the results of this study suggest that HIV prevalence is decreasing in those who are mentally ill and moving towards the general population rates, but this will need to be explored further in larger prospective studies.…”
Section: Discussionmentioning
confidence: 80%
“…The study reported an HIV prevalence range from 23.8% to 39.6%, while the meta-analysis of their data reported the pooled proportion of HIV in patients living with FEP as 26% (95% confidence interval [CI] 10–42). 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis examining the prevalence of HIV seropositivity among patients with first-episode psychosis patients in the African continent found an even greater pooled prevalence of 26%, which they hypothetically linked to longer duration of untreated schizophrenia, low access to health services and high prevalence of infection in the continent. 105 On the other hand, and more encouragingly, the prevalence of HBV and HCV appears to be lower according to more recently published articles (and in the case of HCV, for samples with younger mean age). Global trends for hepatitis B and C have shown a positive evolution over the last decades, 106 especially with the appearance of direct-acting antiviral treatments for HCV.…”
Section: Discussionmentioning
confidence: 91%